Biofuel Successful Strategies towards Sustainable Development: A Bibliometrics Analysis - Muhammad Farhan HR; Eko Priyo Purnomo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
This study aims to analyze biofuel use from oil palm as an alternative source of sustainable development. Data were obtained from the Scopus database with the last five years of publication. This research method uses a qualitative approach to the study of literature. Data analysis used bibliometric analysis with Vosviewer and NVIVO 12 plus software. The findings of this study indicate that several countries have used palm oil-based biodiesel as a transportation fuel, one of which is that Indonesia is the leading country in taking advantage of this opportunity. This can be seen from the development of the B30 from government and biodiesel programs which have become triggers for rising CPO prices worldwide and have impacted Fresh Fruit Bunches at the farm level. The study also found fluctuations in the publication of scientific research on biofuels. The most significant contribution to research articles comes from Malaysia. The university with the most number is University Malaya. The following research areas have the potential for further study: production of biofuels, vegetable oils, renewable diesel, and bio. Production energy, biodiesel, biomass, and biofuels are narratives of scientific research papers related to biofuels.